3-Dimensional organization and dynamics of the microsporidian polar tube invasion machinery - Jaroenlak, Pattana; Cammer, Michael; Davydov, Alina; Sall, Joseph; Usmani, Mahrukh; Liang, Feng-Xia; Ekiert, Damian C.; Bhabha, Gira (PLoS pathogens, 2020)
Microsporidia, a divergent group of single-celled eukaryotic parasites, harness a specialized harpoon-like invasion apparatus called the polar tube (PT) to gain entry into host cells. The PT is tightly coiled within the transmissible extracellular spore, and is about 20 times the length of the spore. Once triggered, the PT is rapidly ejected and is thought to penetrate the host cell, acting as a conduit for the transfer of infectious cargo into the host. The organization of this specialized infection apparatus in the spore, how it is deployed, and how the nucleus and other large cargo are transported through the narrow PT are not well understood. Here we use serial block-face scanning electron microscopy to reveal the 3-dimensional architecture of the PT and its relative spatial orientation to other organelles within the spore. Using high-speed optical microscopy, we also capture and quantify the entire PT germination process of three human-infecting microsporidian species in vitro: Anncaliia algerae, Encephalitozoon hellem and E. intestinalis. Our results show that the emerging PT experiences very high accelerating forces to reach velocities exceeding 300 μm⋅s-1, and that firing kinetics differ markedly between species. Live-cell imaging reveals that the nucleus, which is at least 7 times larger than the diameter of the PT, undergoes extreme deformation to fit through the narrow tube, and moves at speeds comparable to PT extension. Our study sheds new light on the 3-dimensional organization, dynamics, and mechanism of PT extrusion, and shows how infectious cargo moves through the tube to initiate infection.